1995
DOI: 10.1002/pd.1970150510
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis in two cases of de novo complex balanced chromosomal rearrangements. Three‐year follow‐up in one case

Abstract: We report two cases of apparently balanced complex de novo chromosomal rearrangements (BCCR) detected prenatally at 17 weeks and 10 weeks of gestation, respectively. Chromosomes were studied using GTG-banding and fluorescent in situ hybridization (FISH). In one case four chromosomes and in the other case three chromosomes were involved in the rearrangements. One of the pregnancies was terminated and no external or internal showed no abnormalities. The child is now 3 years old and has neither congenital anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Five pregnancies were terminated (Kim et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Phelan et al, 1998;present case); two of them showed no apparent anomalies at autopsy (Batista et al, 1993;Sikkema-Raddatz et al, 1995). Six pregnancies were pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Five pregnancies were terminated (Kim et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Phelan et al, 1998;present case); two of them showed no apparent anomalies at autopsy (Batista et al, 1993;Sikkema-Raddatz et al, 1995). Six pregnancies were pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 previous reports of de novo balanced CCRs identified prenatally none involved mosaicism and only on two did ultrasound indicate a likely abnormal outcome when IUGR was detected prenatally (Kim et al, 1986;Cotter et al, 1996). Follow-up of the remaining cases postnatally revealed that three were dysmorphic with developmental delay (Ruiz et al, 1996;Bogart et al, 1986); one had speech delay (Stoll et al, 1979) but five were clinically normal (Kohler et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Pruggmayer et al, 1990) (Table 1). In two large surveys additional CCRs were noted but no follow-up details were given (Hook and Cross 1987;Warburton, 1991).…”
Section: Discussionmentioning
confidence: 89%
“…Two of the five cases in which the pregnancy was terminated showed no apparent anomalies at autopsy (Batista et al, 1993;Sikkema-Raddatz et al, 1995). In the case reported by Kim et al (1986), the fetus had intra-uterine growth retardation, low-set ears, hypoplastic mandible and widely separated great toes.…”
Section: Commentmentioning
confidence: 88%
“…Of the five cases with postnatal follow-up, one with a maternally transmitted rearrangement was clinically normal at birth (Bellec and de Perdigo, 1991), two were apparently normal at two and three years of age (Sikkema-Raddatz et al, 1995;Kohler et al, 1986), one had growth and speech delay (Bogart et al, 1986), and one had multiple congenital anomalies (Mercier et al, 1996). The anomalies included poorly differentiated ears, short neck, widely spaced nipples, hypospadias, bilateral hydrocele, supernumerary distal forearm crease, bilateral single palmar crease, overlapping fingers and metatarsus valgus.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation